STUDY OF UNIVERSITY STUDENTS’ ATTITUDE TO FLIPPED CLASSROOMS - Fedoriv, Yaroslava; Kytaieva, Susanna; Fedoriv, Mariya (The Modern Higher Education Review, 2025)
This study investigates the complex interplay of psychological and cognitive factors influencing student attitudes and engagement within the flipped classroom model, with a specific focus on the role of "clipped thinking"—a digital-cognitive barrier characterized by fragmented attention. Employing a survey-based methodology in an "English for Academic Communication" course, the research analysed students’ perceptions regarding clarity, relevance, motivation, and learning priorities. The findings indicate that while the model’s success is profoundly shaped by intrinsic characteristics, such as psychological readiness and individual cognitive style, its initial implementation successfully mitigated potential resistance. Specifically, the study confirms that high perceived clarity and relevance of the course design significantly boost initial student acceptance and motivation. Moreover, students prioritise active oral and interactive communication skills, validating the flipped structure's goal of dedicating face-to-face time to high-value application. The theoretical value is provided by integrating emerging digital-cognitive barriers (clipped thinking) with established psychological factors (cognitive load), offering a novel, integrated model for understanding student resistance beyond simple success-or-failure dichotomies. The practical value lies in providing educators with actionable evidence that ensuring clear structure and high perceived relevance is the most efficient instructional strategy for promoting initial acceptance and justifying the pre-class workload across disciplines.